Effects of Lace up Brace on the Ankle Muscles Activity in Different Foot Position during Drop Landing with and without Fatigue - Ali Yalfani; Zahra Raeisi (New Approaches in Sport Sciences)
Background and Purpose: Increasing participation in sports activities has increased the incidence of sports injuries. Considering the short and long term complications of sports injuries, the need to prevent them is one of the most important goals. The purpose of this study was to evaluate the effects of ankle bracing on the ankle plantar flexor muscles activity in different foot position during drop landing with and without fatigue. Method: Fourteen female college athletes participated in this study. Five models of 5 and 10 degrees medial, lateral and normal wedged insoles were used to simulate the position of the feet on the ground at the wrong landing technique. The Medial Gastrocnemius (MG) and Peroneus Longus (PL) muscles activity 100 ms before and 100ms after landing in different foot position before and after muscles fatigue with and without ankle bracing was recorded with surface electromyography. Repeated measures ANOVA was used for statistical analysis (p≤0.05). Results: The results showed that the effect of time on the activity of MG and PL muscles in landing with brace was significant, so that the MG muscle before landing and PL muscle after landing had a higher activity in both times before and after fatigue (p≤0.001). The activity of this muscles was not significant when using the ankle brace during landing in different positions (p˃0.05). Conclusions: According to the results of this study, lace-up brace can help to increase muscles activity when they were fatigue, while the using of brace does not affect muscle activity when landing perform in different positions without fatigue. According to the results, In the case of a suggestion to use brace for athletes, all aspects of using this equipment should be considered.